2014
DOI: 10.1016/j.ygyno.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Combined colonoscopy and endometrial biopsy cancer screening results in women with Lynch syndrome

Abstract: Objective Endometrial biopsy (EMBx) and colonoscopy performed under the same sedation is termed combined screening and has been shown to be feasible and to provide a less painful and more satisfactory experience for women with Lynch syndrome (LS). However, clinical results of these screening efforts have not been reported. The purpose of this study was to evaluate the long-term clinical outcomes and patient compliance with serial screenings over the last 10.5 years. Methods We retrospectively analyzed the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Two other studies evaluated the utility of combining endometrial sampling and colonoscopy in women with LS to allow the procedure to be performed under conscious sedation. They concluded that this combination resulted in a less painful experience than endometrial sampling without sedation in a standard office setting [17,18]. Overall, 78% of the standard endometrial samplings in the present study contained enough tissue for analysis, which is consistent with the levels of 74-90% reported in other studies [26,27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two other studies evaluated the utility of combining endometrial sampling and colonoscopy in women with LS to allow the procedure to be performed under conscious sedation. They concluded that this combination resulted in a less painful experience than endometrial sampling without sedation in a standard office setting [17,18]. Overall, 78% of the standard endometrial samplings in the present study contained enough tissue for analysis, which is consistent with the levels of 74-90% reported in other studies [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…A major disadvantage of such sampling is that it is invasive and painful, irrespective of the indication [15,16]. An alternative strategy to avoid this pain is to perform hysteroscopy, typically with colonoscopy, while under conscious sedation [15,17,18]. Given the pain and invasiveness of these procedures, we wanted to identify an alternative, less painful, and non-invasive method for collecting endometrial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms associated with endometrial cancer allow for earlier diagnosis when the disease is curable, often with surgery alone (30), possibly leading to the impression that endometrial cancer is survivable when diagnosed at the time symptoms present. The relative reluctance to endorse gynecologic screening may also be partly attributed to the dislike of undergoing routine endometrial biopsies, which many women find painful and inconvenient (31,32). In contrast, women in the sample with a prior diagnosis of colorectal cancer had a significantly higher likelihood of endorsing LS screening strategies compared to those without a personal cancer history, as well as higher likelihood of endorsing colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…There is some support for the use of transvaginal ultrasound and endometrial biopsy either annually or every 2 years from the age of 30 to 35 [ 76 ]. In a recent retrospective study over a 10-year period, gynecologists were the designated physicians to perform surveillance colonoscopy and endometrial curettage under sedation to reduce discomfort, at the same outpatient visit scheduled every 1 to 2 years apart [ 77 ]. Endometrial curettage usually provides a large amount of tissue compared to other biopsy methods and is, thus, an added advantage during histological examination.…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 99%
“…The patient with endometrioid carcinoma and three others with complex hyperplasia did not have thickened endometrium on transvaginal ultrasound to warrant a biopsy. With the findings by Nebgen et al [ 77 ] in mind, it is prudent that if it is decided that no active surveillance is to be carried out, female carriers of the DNA MMR gene mutations must be educated on the need to seek immediate medical attention for further investigation if they have any abnormal uterine bleeding.…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 99%